The gut microbiome alters immunophenotype and survival from sepsis - Fay, Katherine T. (FASEB J, 2019)
The microbiome is increasingly implicated in immune regulation and mortality from sepsis. Mice with identical genetic backgrounds but distinct microbiomes were obtained from different vendors and analyzed following cecal ligation and puncture (CLP). β diversity of the microbiome measured from feces demonstrated significant differences between The Jackson Laboratory (Jax; Bar Harbor, ME, USA) and Charles River Laboratories (CR; Wilmington, MA, USA) C57/B6 mice. Jax mice had 7-d mortality of 90% following CLP, whereas CR mice had a mortality of 53%. Differences in vendor were associated with altered immunophenotype with increased splenic IFN-γ(+)CD4(+) T cells, effector memory CD4(+) T cells, and central memory CD4(+) T cells and increased Peyer’s patch effector memory CD4(+) T cells in septic CR mice. To determine whether differences in the microbiome were responsible for these differences, Jax and CR mice were cohoused for 3 wk, after which they assumed a similar microbiota composition. Cohoused mice had improved survival following CLP compared to Jax mice and had similar survival regardless of their vendor of origin. All differences in immunophenotype between septic Jax and CR mice disappeared following cohousing. These findings suggest that the microbiome plays a crucial role in survival and the host immune response from sepsis and represents a potential target for therapeutic intervention.—Fay, K. T., Klingensmith, N. J., Chen, C.-W., Zhang, W., Sun, Y., Morrow, K. N., Liang, Z., Burd, E. M., Ford, M. L., Coopersmith, C. M. The gut microbiome alters immunophenotype and survival from sepsis.